MEMPERKOKOH POSISI TAWAR POLITIK PEGIAT SISTEM PENYEDIAAN AIR MINUM BERBASIS MASYARAKAT LEWAT KOMUNIKASI LINGKUNGAN - Effendy, Rochmad; Amin, Rofikul; Indra Kusuma, Ginanjar (Unitri Press, 2019)
The limited ability in providing a good water services to all citizens, as well as the fact that water is a public good, the involvement of citizens in drinking water supply is one way to achieve this goal. The existence of a community-based drinking water supply system in the form of the Community Drinking Water User Association (HIPPAM) needs to be maintained to ensure the sustainability of its social services. The sustainability of the HIPPAM social enterprise is determined by internal aspects such as governance and institutional performance, financial management, technical performance of water distribution services. Other things related to external aspects such as the support of stakeholders such as customers, community members, environment activist and village government related to the issue of conservation as well as environmental sustainability and good water governance. Discussing these issues with all stakeholders in drinking water in the available local public space can be referred to as environmental communication that is hoped will be able to create awareness and citizen?s collective action citizens on the importance of good water governance. This study uses qualitative data with interviews and in-depth interviews as data collection techniques, the informants of this study consisted of the management of the HIPPAM Mangga Dua. The result showed that administrators had sufficient environmental and ecological literacy. For them, water is spiritual and social energy sources that enable them to develop dan enhance the community?s social capital.